Performance metric analysis for a jamming detection mechanism under collaborative and cooperative schemes in industrial wireless sensor networks - Cortés-Leal, Alejandro; Del-Valle-soto, Carolina; Cardenas, Cesar; Valdivia, Leonardo J.; Del Puerto-Flores, Jose Alberto (Sensors, 2023)
The emergence of Industry 4.0 technologies, such as the Internet of Things (IoT) and Wireless Sensor Networks (WSN), has prompted a reconsideration of methodologies for network security as well as reducing operation and maintenance costs, especially at the physical layer, where the energy consumption plays an important role. This article demonstrates through simulations and experiments that, while the cooperative scheme is more efficient when a WSN is at normal operating conditions, the collaborative scheme offers more enhanced protection against the aggressiveness of jamming in the performance metrics, thus making it safer, reducing operation and maintenance costs and laying the foundations for jamming mitigation. This document additionally offers an algorithm to detect jamming in real time. Firstly, it examines the characteristics and damages caused by the type of aggressor. Secondly, it reflects on the natural immunity of the WSN (which depends on its node density and a cooperative or collaborative configuration). Finally, it considers the performance metrics, especially those that impact energy consumption during transmission.
Keywords: cooperative communication; industrial nternet of things (IIoT); industrial wireless sensor networks; jamming; security for IIoT; Scopus